Modeling the Lattice Volume Effect on the Melting Temperature of Gold Nanoparticles - A. Kh. Alassafee; M. S. Omar (College of Education for Pure Sciences, 2013)
Abstract The modification of lattice vibration based model used to predicate the dependence of melting temperature on the size and mean square displacement of the free standing gold spherical nanoparticle. The models predicate that the melting temperature decreases with the reduce of nanoparticles size due to the change of its lattice volume, calculated values of melting agree fairly well with the available experimental data